Becoming Asian (American)? Inter-ethnic differences in racial, ethnic, and American identities for Asian American adults. (June 2022) - Casarez, Raul S; Farrell, Allan; Bratter, Jenifer L; Zhang, Xiaorui; Mehta, Sharan Kaur
Asian Americans' incorporation into American society is structured by interactions with a racial hierarchy that presents greater barriers for some ethnic groups more than others. The racialized assimilation framework predicts that experiences of discrimination shape incorporation into US society. This study investigates the impact of discrimination on the importance placed on three identities—racial, ethnic, American identity—relative to indicators of structural assimilation. Using the post-election wave of the 2016 National Asian American Survey ( N = 3923), we estimate multivariable models to explore the centrality of racial, ethnic, and American identity among an ethnically diverse sample of Asian Americans. Regardless of ethnic group, a large majority deem American as a central identity, with greater variation in race and ethnicity centrality. Discriminatory encounters increased centrality of racial and American identity; meanwhile, educational attainment drives down the centrality of racial identity, though exerting no impact on American identity centrality. Ethnicity moderates these relationships as discrimination enhances racial identity centrality for Koreans, Indians, and Japanese but drives down racial centrality for Chinese adults. Findings reveal that racialized encounters are a distinctive component of the assimilation process resulting in variable expressions of identity among Asian Americans, revealing identity variation across Asian American ethnic groups.